Penerapan Model Blended Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Ekonomi - Yosi Shandra; Mega Adyna Movitaria (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
The problem in this study is that students are not active in discussing due to a lack of understanding of learning materials because learning materials and activities controlled by students consist of online. The purpose of this study was to describe the implications of the Blended learning model to improve economy learning outcomes in class XI of SMA Negeri 10 Padang. This type of research is Classroom Action Research (CAR). Which consists of 2 cycles. The subjects of this study were students of class XI SMA Negeri 10 Padang. The results of this study can be concluded that student learning outcomes in the cognitive domain of students in the first cycle, the average grade obtained is 73.5, increasing in the second cycle to 84.5. Student learning outcomes in the affective domain of students in the first cycle, the class average score obtained was 72.92 and increased in the second cycle to 87.75. Student learning outcomes in the psychomotor domain of students in the first cycle, the average grade obtained was 74.58, which increased in the second cycle to 75.83. So it can be concluded that the Blended learning model can improve student learning processes in learning Economy